Экспериментальная оценка электрического сопротивления и электропроводности сильноточного плазменного канала в цепи разряда мощного генератора тока искусственной молнии - Баранов, М.И.; Колиушко, Г.М.; Лысенко, В.О.; Носенко, М.А. (Електротехніка і електромеханіка, 2011)
Experimental a way the close numeral values of linear active electric resistance and specific conductivity of heavy-current plasma channel of an air heavy-current of discharge are got in the chain of powerful capacity store of energy, in-use at forming repeated impulsive components of current of artificial lightning with the rationed amplitude to 100 k􀈺.